2017
DOI: 10.1021/jacs.7b02470
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Migration and Amplified Quenching on Two-Dimensional Metal–Organic Layers

Abstract: The dimensionality dependency of resonance energy transfer is of great interest due to its importance in understanding energy transfer on cell membranes and in low-dimension nanostructures. Light harvesting two-dimensional metal-organic layers (2D-MOLs) and three-dimensional metal-organic frameworks (3D-MOFs) provide comparative models to study such dimensionality dependence with molecular accuracy. Here we report the construction of 2D-MOLs and 3D-MOFs from a donor ligand 4,4',4″-(benzene-1,3,5-triyl-tris(eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
120
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(128 citation statements)
references
References 66 publications
6
120
0
2
Order By: Relevance
“…Bottom‐up approaches include modulated synthesis and interfacial synthesis. By adding acid, salt, or triethylamine as modulators during MOF growth, a MOF 2‐D secondary architecture can be obtained. Interfacial synthesis has also been investigated using liquid/liquid interfaces and gas/liquid interfaces (mainly the Langmuir–Blodgett method) .…”
Section: Mofs With Hierarchical Architecturesmentioning
confidence: 99%
“…Bottom‐up approaches include modulated synthesis and interfacial synthesis. By adding acid, salt, or triethylamine as modulators during MOF growth, a MOF 2‐D secondary architecture can be obtained. Interfacial synthesis has also been investigated using liquid/liquid interfaces and gas/liquid interfaces (mainly the Langmuir–Blodgett method) .…”
Section: Mofs With Hierarchical Architecturesmentioning
confidence: 99%
“…[44][45][46][47][48][49][50][51][52][53][54] Rational design of 2D and 3D MOFs can provide excellent exciton transport, [45] a phenomenon that is most efficient for MOFs which contain chromophore-based ligands separated by 1-2 nm distances. [44][45][46][47][48][49][50][51][52][53][54] Rational design of 2D and 3D MOFs can provide excellent exciton transport, [45] a phenomenon that is most efficient for MOFs which contain chromophore-based ligands separated by 1-2 nm distances.…”
Section: Excitonsmentioning
confidence: 99%
“…The structure was extracted from crystallographic information file (CIF) [44]. The structure was extracted from crystallographic information file (CIF) [44].…”
mentioning
confidence: 99%
“…Lin at al. have investigated the difference of exciton migration and fluorescence quenching efficiency between 2D MOF nanosheets and 3D bulk MOFs (Figure a) . They synthesized 2D Hf‐based MOF nanosheets with the thickness of 2±0.2 nm and 3D Hf‐based MOF from similar hafnium SBUs and the same ligands with the nanosheets.…”
Section: Sensing Platformsmentioning
confidence: 99%
“…have investigated the difference of exciton migration and fluorescenceq uenching efficiency between 2D MOF nanosheets and3 Db ulk MOFs (Figure 5a). [106] They synthesized 2D Hf-based MOF nanosheets with the thickness of 2 AE 0.2 nm and 3D Hf-based MOF from similarh afnium SBUs and the same ligands with the nanosheets. They found that althought he exciton migrations in 2D materials is slower and the total energy transfer in the 2D MOF nanosheets is lower than 3D bulk MOFs, the 2D MOF nanosheets exhibits much more efficient energy transfer than the bulk one, leading to the amplifiedf luorescenceq uenching effect (Figure 5b).…”
Section: Sensing Platformsmentioning
confidence: 99%